2010
DOI: 10.1007/s00125-010-1684-1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, lipotoxicity, type 2 diabetes and atherosclerosis: the missing links. The Claude Bernard Lecture 2009

Abstract: Insulin resistance is a hallmark of type 2 diabetes mellitus and is associated with a metabolic and cardiovascular cluster of disorders (dyslipidaemia, hypertension, obesity [especially visceral], glucose intolerance, endothelial dysfunction), each of which is an independent risk factor for cardiovascular disease (CVD). Multiple prospective studies have documented an association between insulin resistance and accelerated CVD in patients with type 2 diabetes, as well as in non-diabetic individuals. The molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
642
0
37

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 751 publications
(696 citation statements)
references
References 213 publications
(324 reference statements)
17
642
0
37
Order By: Relevance
“…The possibility that hyperinsulinaemia promotes atherosclerosis is tempered by observations that insulin can be protective in some animal models [6], although insulin resistance itself is usually considered an adverse CVD phenotype. For instance, insulin resistance may act through inflammatory or endothelial dysfunction pathways to promote atherosclerosis [7]. Recent meta-analyses suggest the association of HOMA-IR and fasting insulin with CVD is likely to be modest, although many individual studies had limited power [8,9]; for example, the most powerful study relating HOMA-IR to CVD had only 318 events during a 30 year follow-up [9].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that hyperinsulinaemia promotes atherosclerosis is tempered by observations that insulin can be protective in some animal models [6], although insulin resistance itself is usually considered an adverse CVD phenotype. For instance, insulin resistance may act through inflammatory or endothelial dysfunction pathways to promote atherosclerosis [7]. Recent meta-analyses suggest the association of HOMA-IR and fasting insulin with CVD is likely to be modest, although many individual studies had limited power [8,9]; for example, the most powerful study relating HOMA-IR to CVD had only 318 events during a 30 year follow-up [9].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance or the compensating hyperinsulinaemia leads to the manifestation of a cluster of risk factors, including hyperglycaemia, hypertriacylglycerolaemia, low plasma levels of HDL-cholesterol and arterial hypertension, that has been termed the metabolic syndrome. Although much progress [5] has been made in the understanding of the mutual relationships between obesity, insulin resistance, type 2 diabetes and atherosclerosis, the complete picture remains elusive. In the last years the carbohydrate-centred view of the pathogenesis of diabetes has widened to include different classes of lipids [5][6][7] and inflammatory factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although much progress [5] has been made in the understanding of the mutual relationships between obesity, insulin resistance, type 2 diabetes and atherosclerosis, the complete picture remains elusive. In the last years the carbohydrate-centred view of the pathogenesis of diabetes has widened to include different classes of lipids [5][6][7] and inflammatory factors [8]. Mounting evidence suggests that sphingolipids play a role in the pathogenesis of insulin resistance and diabetes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…4 Insulin-resistant individuals have a reduced rate of fat oxidation, compared with normal, insulin-sensitive individuals, and thus, the decreased mitochondrial fat oxidative capacity could lead to an increase in the intracellular fat content. 5 It has also been reported that IHL accumulation is associated with impaired hepatic glucose metabolism. The suppressive effect of insulin on hepatic glucose production was shown to be negatively correlated with the IHL content in both healthy subjects and patients with type 2 diabetes.…”
mentioning
confidence: 98%